The Glu727 Allele of Thyroid Stimulating Hormone Receptor Gene is Associated with Osteoporosis - Liu, Ren-De (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Published data indicate that thyroid stimulating hormone receptor (TSHR) activities are associated with osteoporosis in some patients. AIM: This study aimed to elucidate whether a given polymorphism of the TSHR gene is associated with osteoporosis. MATERIALS AND METHODS: One hundred and fifty subjects with osteoporosis were recruited in this study. The diagnosis of osteoporosis was performed with quantitative ultrasound system. The TSHR gene polymorphism was examined by polymerase chain reaction–restriction fragment length polymorphism. RESULTS: The results showed a nucleotide substitution in the first position of codon 36 of the TSHR gene. The nucleotide substitution was from G to C, leading to a (36)D → (36)H change (D36H) in the predicted amino acid sequence of the receptor. The change did not show significance between healthy subjects and patients with osteoporosis (P > 0.05). On the other hand, we identified another single nucleotide polymorphism that is a C-to-G substitution at codon 727 (GAC to GAG); its frequency was significantly higher in patients with osteoporosis than that in healthy subjects. Using logistic regression analysis, significant correlation was revealed between the genotype D727E and the serum levels of TSH, or the quantitative ultrasound value of the calcaneal bone. CONCLUSIONS: The present study suggests that the genotype D727E of the TSHR, but not the genotype D36H, may be a genetic risk factor for osteoporosis.